A Critical Analysis of Education Accessibility and Relevance Policies in Indonesia: Post-Pandemic Challenges and the Era of Disruption: (Analisis Kritis Kebijakan Aksesibilitas dan Relevansi Pendidikan di Indonesia: Tantangan Pasca-Pandemi dan Era Disrupsi) - Almas Hadian Muhtadi; Alif Nur Shobari (Al Kautsar: Knowledge Advancements in Teaching Strategies and Research, 2025)
Education in Indonesia faces various challenges, including large geographical areas, economic disparities and gender inequality. Education accessibility remains a significant issue in rural and remote areas, where education facilities are often inadequate and qualified teaching personnel are hard to find. In addition, the relevance of the curriculum to the needs of the labor market and technological developments, the quality of teachers' competencies and others are also still a concern. This research aims to explain the dynamics of accessibility and relevance of education in Indonesia. The type of research used is library research, then using a qualitative approach with an inductive thinking method. This research examines various factors that affect the accessibility and relevance of education in Indonesia and offers solutions to improve quality and equality in education. Some of the government's efforts in improving the accessibility and relevance of education in Indonesia by implementing various programs include: School Development Program (Presidential Instruction No. 10, 1973), illiteracy eradication program, compulsory education program, education pathway equalization program, smart Indonesia program (PIP), zoning school program, independent learning program, teacher program and driving school.